Inovasi Pembelajaran melalui Benchmarking Pada Program Studi Pariwisata Syariah IAIN Parepare - Muh Asrul (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2023)
This article aims to describe Benchmarking activities for the Sharia Tourism Study Program. Benchmarking was carried out in Makassar City, by integrating learning innovation models in the implementation of these activities. The method used is qualitative in the form of field studies, then writes them in narrative form. The results of the study show that learning innovation can be carried out in a series of Benchmarking activities. Unfortunately, there is a gap in terms of learning practices because the Islamic Tourism Study Program does not yet have the availability of laboratory facilities and infrastructure such as lab kitchens, rooms, and making bed equipment and housekeeping. Therefore, it is necessary to hold a tourism laboratory or procure the practicum equipment